Elements of Child-Friendly Environment: The Effort to Provide an Anti-Violence Learning Environment - Purnama, Sigit (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
This article reported the important of child-friendly environment to reduce violence against children. A child-friendly environment is able to change an aggressive behavior to be a positive behaviour. In the opposite, an unfriendly environment, will increase the aggressive behavior in children. Both indoor and outdoor environment are as one of the circle dimension that are able to stimulate the early childhood development with a positive behaviour. The environment is constructed from some elements, such as line, shape and color. Each of them has psychological impression that varies and at once is able to affect the mental aspect of a child. With the effective elements, variation and its balance, will establish a child-friendly environment. The enviromnet that secure and comfortable that will be able to stimulate the early childhood development and also to reduce their aggressive behaviour. Keywords: elements, a child-friendly environment, violence. Artikel ini memaparkan pentingnya lingkungan yang ramah untuk mengurangi perilaku kekerasan yang terjadi pada anak usia dini. Lingkungan yang ramah mampu mengubah perilaku agresif menjadi positif. Sebaliknya, lingkungan yang tidak ramah anak, justru akan meningkatkan perilaku agresif. Lingkungan indoor dan outdoor merupakan salah satu dimensi lingkungan yang dapat menstimuli perkembangan anak usia dini agar terbentuk perilaku positif. Lingkungan tersebut dibangun oleh beberapa elemen, seperti garis, bentuk, dan warna. Masing-masing elemen memiliki kesan psikologi yang bervariasi dan sekaligus dapat mempengaruhi psikologi anak. Penggunaan elemen-elemen yang tepat, bervariasi, dan seimbang akan membentuk lingkungan yang ramah anak, yakni lingkungan yang aman, nyaman, yang akan dapat menstimuli perkembangan dan mengurangi perilaku agresif anak usia dini. Kata Kunci: elemen, lingkungan ramah anak, kekerasan.